Reflections on Endogenous Crises Explanations in a World of Liberal Orders - Michael Zürn (Global Studies Quarterly, 2024)
One major contribution of this special forum is to develop the potential of endogenous explanations further. In doing so, most contributions focus on institutional dynamics and temporal sequences instead of “comparative statics.” In this commentary, I want to delve deeper into the logic of endogenous explanations of contestations and crises. Based on a general understanding of the concept of endogenous explanation, the article distinguishes different endogenous accounts and locates the contributions to this forum within such a map. – – L'une des principales contributions de ce numéro spécial se situe dans l'approfondissement du potentiel des explications endogènes. Ce faisant, la plupart des contributions se concentrent sur la dynamique institutionnelle et des séquences temporelles, et non des « statiques comparatives ». Dans ce commentaire, je souhaite approfondir la logique des explications endogènes des contestations et crises. En se fondant sur une interprétation générale du concept d'explication endogène, l'article fait la distinction entre différents récits endogènes et resitue les contributions de ce numéro spécial au sein d'une telle configuration.
Keywords: 300